2014 IEEE Intelligent Vehicles Symposium Proceedings 2014
DOI: 10.1109/ivs.2014.6856522
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating human & computer for expressway lane changing

Abstract: Google already showed the self-driving car can do stopping and accelerating more smoothly than the human drivers by doing extensive experiments. In this paper, we compare a human driver with computer generated motion for expressway lane changing. We did experiments at Nagoya ring route expressway and recorded all the detail motion information regarding lateral and longitudinal movement of a taxi driver. We developed an algorithm to generate and evaluate the alternative lane change motion sets considering both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Lefèvre et al [30] present a framework for autonomous driving which can learn from human demonstrations, and apply the demonstrations to the longitudinal control of an autonomous car. Tehrani et al [32] compare the actions of a human driver with computer generated motions for expressway lane changing. By analyzing the human-driver lane change data, Do et al [33] propose a two-segment lane change model that mimics the human driver.…”
Section: Introductionmentioning
confidence: 99%
“…Lefèvre et al [30] present a framework for autonomous driving which can learn from human demonstrations, and apply the demonstrations to the longitudinal control of an autonomous car. Tehrani et al [32] compare the actions of a human driver with computer generated motions for expressway lane changing. By analyzing the human-driver lane change data, Do et al [33] propose a two-segment lane change model that mimics the human driver.…”
Section: Introductionmentioning
confidence: 99%
“…They propose to provide "ease and comfort" by producing jerk-optimal trajectories. Later, lane change experiments conducted by Tehrani et al, in Japanese highways showed that the human lane change behavior cannot be modelled by a single stage of jerk-optimal trajectories [5,6]. Instead they proposed a two-stage model.…”
Section: Introductionmentioning
confidence: 99%